2008
DOI: 10.1021/jp710373e
|View full text |Cite
|
Sign up to set email alerts
|

Bond Dissociation Energies in Second-Row Compounds

Abstract: Heats of formation at 0 and 298 K are predicted for PF3, PF5, PF3O, SF2, SF4, SF6, SF2O, SF2O2, and SF4O as well as a number of radicals derived from these stable compounds on the basis of coupled cluster theory [CCSD(T)] calculations extrapolated to the complete basis set limit. In order to achieve near chemical accuracy (+/-1 kcal/mol), additional corrections were added to the complete basis set binding energies based on frozen core coupled cluster theory energies: a correction for core-valence effects, a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
81
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 111 publications
14
81
0
Order By: Relevance
“…From 1b to 1f, the energy differences in both eq PH 3 and ax PH 3 LDEs are less than 3 kcal/mol. In most cases, the strength of the bonds is reflected by bond lengths and LDEs, but this may not always be true [86]. The carbonyl cis to the ax (eq) PH 3 is replaced by PH 3 to form 1e from 1b and 1c.…”
Section: Resultsmentioning
confidence: 99%
“…From 1b to 1f, the energy differences in both eq PH 3 and ax PH 3 LDEs are less than 3 kcal/mol. In most cases, the strength of the bonds is reflected by bond lengths and LDEs, but this may not always be true [86]. The carbonyl cis to the ax (eq) PH 3 is replaced by PH 3 to form 1e from 1b and 1c.…”
Section: Resultsmentioning
confidence: 99%
“…Similar problems have been discussed for the ABDEs of alkenes [47][48][49] and secondrow compounds. [50] In the case of CH 2 CH 2 and CF 2 CF 2 , the ADBE of ethylene is much larger as compared with tetrafluoroethylene. However, when diabatic dissociation is considered, the DBDEs are similar because CF 2 CF 2 dissociates to 3 CF 2 instead of 1 CF 2 as in the adiabatic process.…”
Section: Diabatic Bond Dissociation Energiesmentioning
confidence: 99%
“…To do so, we first estimated the SÀO bond energy as the average of the values determined for SOH [52] and HSOH, [28] which are 76.0 and 69.6 kcal mol . This stems from the fact that it represents more closely the bonding in HCSOH, which, as indicated by Grant et al, [50] is the most important aspect to take into account when dealing with DBDEs. If the latter value is adopted as the reference value, the DBDE of HCSOH is weaker than those of CS, SCS, and SCO, but stronger than that of CH 2 S. Therefore, none of the three approaches used to compute the DBDE of HCSOH supports the presence of a CS bond.…”
mentioning
confidence: 99%
“…17 Most studies have focussed on sulfur-containing compounds, [18][19][20] however some also tackled this issue for phosphorus-containing species. 9,21,22 It was overall found that the use of high-exponent d functions is very important in the determination of accurate energetics, whereas the impact on structures, i.e., bond lengths and angles, is slight. The present paper uses a large basis set, without however the explicit inclusion of tight d functions, focussing on the assessment of the electronic structure method.…”
Section: Introductionmentioning
confidence: 99%